A gender perspective on Social Work and the right to care - Roca-Escoda, Mireia; Hernández-Cordero, Ana Lucía (Cuadernos de Trabajo Social, 2025)
This article analyses the reproduction of gender inequalities in the Home Help Service and the responsibility of social work in this context. The tension between the personal autonomy of dependent persons and the promotion of gender equality in these services is studied. Although freedom of choice is crucial to guarantee personal autonomy, it can also reinforce traditional roles that assign women as the main caregivers, perpetuating the feminisation of care. Through a qualitative methodology based on in-depth interviews with female social workers, we analyse their discourses and practices when selecting the professional person in charge of providing care in the home. The results show the Home Help Service is perceived as a ‘women’s’ job and that users tend to prefer female carers, which reinforces gender stereotypes in the sector and contributes to maintaining inequalities in the distribution of care work. The study highlights the need for social work to promote a balance between the right to free choice and social justice, thus avoiding the reproduction of traditional roles. The importance of gender mainstreaming in social work is highlighted and ‘relational autonomy’ is proposed as an alternative, taking into account interdependence and social responsibility in care decisions.